Identification of The Potential of Mangrove At Pantai Sari, Pakis, Banyuwangi, Jawa Timur. - Mega Yuniartik; Agustina Tri Kusuma Dewi; Magdalena Putri Nugrahani; Ervina Wahyu Setyaningrum (Sriwijaya Journal of Environment, 2021)
Banyuwangi is an area that has the longest coastline in East Java, with a length of 175.8 km. one of the coastal potentials is the mangrove ecosystem. Pantai Sari is one of the locations that has the potentials to be developed in Banyuwangi regency. This beach is a forest area in the city of Banyuwangi. In general, they have natural charateristics, many pine trees have been planted since 2015. The purpose of this study was to obtain data on the diversity of mangroves in river and coastal areas at Pantai Sari. The method used is descriptive quantitative, with data collection using nested plot method with a distance of 20 m between plots. The results showed that there are 7 species mangroves were found in the river, namely Avicennia officinalis, Rhizophora apiculata, Sonneratia caseolaris, Lannea coramandelica, Erythrina costaricensis, dan Thespesia populnea. The highest number of individuals was Rhizophora apiculata with number 1,291 individu, and the lowest number was Erythrina costaricensis and Thespesia populnea. The other hand, there was 5 species mangroves in the coastal area, namely Casuarina cunninghamiana, Casuarina equisetifolia, Lannea coramandelica, Terminalia catappa, dan Thespesia populnea. The highest number of individuals was pine beach (Casuarina equisetifolia) with number 122 individu, and the lowest number was waru laut (Thespesia populnea) with number 1 individu